The Efficacy of Intra-Articular Injections for Pain Control Following Hip Arthroscopy for Femoroacetabular impingement - Nho, Shane Jay (Orthop J Sports Med, 2017)
OBJECTIVES: There is a rising trend among surgeons to administer intra-articular local anesthetic to help alleviate postoperative pain following hip arthroscopy. The purpose of this study was to evaluate the analgesic efficacy of intra-articular Marcaine for postoperative pain control after hip arthroscopy for femoroacetabular impingement (FAI). METHODS: A prospective cohort study was performed. A total of one hundred consecutive patients who underwent hip arthroscopy by a single surgeon for FAI were included in this study. Patients were divided into two groups, with one group receiving intra-articular Marcaine (0.5% Marcaine plain) and the other group receiving intra-articular saline. The primary outcome measure was VAS pain measured at specific time intervals immediately upon arrival to the post-anesthesia care unit (PACU), at 10, 20, and 30 minutes postoperatively, and at the 1 week follow up visit. Propensity scores were generated from baseline patient demographics and comorbidities, and patients were matched 1:1 based on propensity scores in order to reduce potential confounding. RESULTS: A total of 100 patients were included. Of these, 38% were males and the average age was 29.7 + 12.1. 50 patients received intra-articular Marcaine while the other 50 did not. Before and after matching, there were no statistically significant difference in age, BMI, gender and preoperative VAS pain between the cohorts (Table 1). No differences in preoperative and postoperative VAS pain were found between the Marcaine and non-Marcaine cohorts within the immediate postoperative period. However, there was significant reduction in the absolute VAS at 1 week follow up in the Marcaine cohort compared to the non-Marcaine cohort. All patients were discharged home and did not experience any complications from the procedures. CONCLUSION: This study suggests that injecting intra articular Marcaine during hip arthroscopy for FAI may not be necessary as it may only provide minimal pain control.